The The Effect of Cooperative Learning with Jigsaw Technique on Enhancing Student Engagement in Arabic Language Course: A Case Study of Second Semester Students in the Islamic Education Program at the Riyadlotul Mujahidin Ngabar Ponorogo Islamic Institute - Ratna Utami Nur Ajizah, Ratna (Nahdlatul Lughah, 2024)
Abstract: This research investigates the implementation of the Jigsaw technique in Arabic language learning to enhance students' activeness in the second semester of the Islamic Education Study Program at Riyadlotul Mujahidin Islamic Institute in Ngabar, Ponorogo. The study aims to improve students' participation and engagement in the learning process. Following a Classroom Action Research approach, three cycles were conducted, involving planning, implementation, observation, and reflection. Findings indicate that the Jigsaw technique positively impacted students' activeness in the Arabic language course. Assessments in the third cycle revealed improvements in reading Arabic materials, asking questions for clarification, active participation in group discussions, attentive listening, note-taking, completing assignments, collaborative teamwork, expressing opinions confidently, and responding effectively to peers. These results highlight the significant effect of using the Jigsaw technique to enhance students' participation and activeness in the Arabic language class. The research emphasizes the importance of interactive and collaborative teaching strategies to create an engaging learning environment. By implementing the Jigsaw technique, lecturer can enchance students' involvement and promote active learning in the Arabic language course.